Facilitating social interactions of adults with developmental disabilities in the community - Gomez, Ophelia N. (ProQuest Information and Learning Company, 2002)
This study investigated the effectiveness of a training package designed to teach community living support staff to facilitate social interactions between adults with developmental disabilities and community members in various community settings. Staff participants were taught to use facilitative leads such as: (a) paraphrase, (b) interpretation, (c) verbal prompt, and (d) information-giving designed to support interactions between dyads. Participants were four support staff and four dyads that consisted of an adult with developmental disabilities and a community member. Each staff participant was paired with a dyad. The training package consisted of (a) an in-service training that included lectures, modeling, and role-play, and (b) feedback following community-training sessions. The effectiveness of this intervention was evaluated based on the (a) staff participants' facilitative and non-facilitative behaviors, (b) dyads' reciprocal interactions (i.e., single and extended interactions) and non-reciprocal verbalizations, novel topics within the dyads' extended interactions, and length of the dyads' extended interactions; and (c) behaviors of staff participants and dyads during generalization probes. Social validity measures were used to evaluate the perceived effectiveness and acceptability of the training package. A multiple baseline design across triads (i.e., staff members and dyads) with a control triad was employed to evaluate the effects of the intervention on both staff and dyad behaviors. Results showed that all three staff participants increased their use of facilitative leads after training and maintained on assessments ranging from 5 to 14 weeks following training. In contrast, the fourth staff participant who was assigned in the control triad, remained to have high levels of non-facilitative leads and low levels of facilitative leads. The results further showed that after staff participants' training, the three dyads increased the proportion of their extended interactions, while single reciprocal interactions remained unchanged. Further, the length of the dyads' extended interactions increased. During dyads' interactions, novel topics were consistently emerging after staff participants' training. During generalization probes, results showed that the novel dyads increased their extended interactions. Both staff participants and community members rated the training favorably. The implications of the findings are discussed in terms of the emerging role of supported living staff as social inclusion facilitators and social interaction as a means to building social relationships.--Abstract.